SHOPPING MALL PREMISES SCADA-MICROCLIMATECONTROL SYSTEM DEVELOPMENT - YEVSEIENKO, Oleh; KACHANOV, Petro (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to the shopping malls technological processes of heating, air conditioning and ventilation control studying. In order to develop a shopping mall microclimate control automated system temperature, humidity and ventilation control laws were analysed. Literature review shows that current microclimate control systems are not energy efficient and the usage of supervisory control and data acquisition systems can provide information of the current system state and decrease energy consumption. It is stated that using SCADA-system helps to reduce equipment operating costs by collecting and processing real-time information and implementing new energy-efficient control laws. To achieve this goal, the existing microclimate control systems were analysed. It was determined that these systems can be improved by using the SCADA system. Current implementations of shopping malls control parameters are investigated. Based on investigated control parameters the requirements of SCADA-systems construction were received. It was shown that the developed control system simplifies shopping malls microclimate control system construction, control object identification and energy-efficient control algorithms implementation. An overview of temperature and humidity processes in the shopping malls control algorithms was made. The list of input-output parameters of ventilation system control has been made. Using these parameters, the structural scheme of connection was built. The equipment of an automated control system is described. Operator visualization for microclimate parameters tracking have been developed. Visualizations of the authorization, room selection and setting control settings have been designed. The practical significance of the study lies in the hardware and software system control development.